1976
DOI: 10.2337/diab.25.7.566
|View full text |Cite|
|
Sign up to set email alerts
|

Diabetes Mellitus: Incidence, Prevalence, Survivorship, and Causes of Death in Rochester, Minnesota, 1945–1970

Abstract: The incidence and prevalence of diabetes mellitus in residents of Rochester, Minnesota, for 25 years (1945 to 1970) were determined from available medical records. The over-all incidence rate for diabetes is 133 new cases per 100,000 population per year (age-adjusted to 1970 U.S. white population). The rate increased with age for both men and women and was higher among men over 30 years of age. The average annual incidence rates per five-year period for juvenile-onset diabetes mellitus were low and variable an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

7
83
2
2

Year Published

1979
1979
2008
2008

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 179 publications
(94 citation statements)
references
References 0 publications
7
83
2
2
Order By: Relevance
“…In patients with Type II diabetes the percentage of deaths from renal causes is 8 % for men and 14 % for women. This is higher than in some older studies [22] but the difficulty in characterising the exact nature of the`renal' death in the WHO cohort makes comparison difficult. The percentage of renal deaths in the Hong Kong men and in the Pima Indians of both sexes is about double the average but both had a lower proportion of cardiovascular deaths.…”
Section: Discussionmentioning
confidence: 63%
“…In patients with Type II diabetes the percentage of deaths from renal causes is 8 % for men and 14 % for women. This is higher than in some older studies [22] but the difficulty in characterising the exact nature of the`renal' death in the WHO cohort makes comparison difficult. The percentage of renal deaths in the Hong Kong men and in the Pima Indians of both sexes is about double the average but both had a lower proportion of cardiovascular deaths.…”
Section: Discussionmentioning
confidence: 63%
“…Further, good medical practice now requires that patients hospitalized for CVD be evaluated for diabetes. Other U.S. studies have also reported poor death certificate sensitivity for diabetes (4,17,18,20,23,32) and documented the resultant bias when mortality data are used to estimate the burden of diabetes in the population. The present study, which is the only longitudinal study to include data from the last decade, shows no improvement of overall diabetes reporting on death certificates.…”
Section: Discussionmentioning
confidence: 99%
“…The few previous longitudinal studies of diabetes reporting on death certificates were conducted in foreign countries, making comparisons with U.S. data difficult (13)(14)(15)(16), were based on data collected before 1994 (17,18), or were from diabetic populations only (4). In these studies the correct reporting of diabetes on death certificates ranged from 35 to 65%.…”
mentioning
confidence: 99%
“…In the recent diabetes survey in Malta, where Type 2 diabetes is known to be very common, the prevalence was 19% in men aged 65 to 74 years [20]. All other earlier prevalence studies in elderly Caucasoid populations, unfortunately using varying methods and criteria, reported less than 15% diabetes for men aged 65 years or more [21][22][23][24][25][26][27][28][29][30]. Some of the surveys in the male populations of the Pacific Islands showed a very high prevalence in middle-aged men [31], but usually a lower prevalence of diabetes in the elderly than that in Finnish men.…”
Section: Discussionmentioning
confidence: 99%